2003
DOI: 10.1098/rspb.2003.2495
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the primary sonic muscles inCarapus acus(Carapidae): a multidisciplinary approach

Abstract: Sound production in carapid fishes results from the action of extrinsic muscles that insert into the swim bladder. Biochemical, histochemical and morphological techniques were used to examine the sonic muscles and compare them with epaxial muscles in Carapus acus. Sonic fibres are thicker than red and thinner than white epaxial fibres, and sonic fibres and myofibrils exhibit an unusual helicoidal organization: the myofibrils of the centre are in a straight line whereas they are more and more twisted towards th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 38 publications
3
32
0
Order By: Relevance
“…In Carapus acus (Carapidae), Parmentier et al (Parmentier et al, 2006a) demonstrated that sonic muscles inserting on the swimbladder can also produce sounds at very low contraction rates (sonic muscle tetanized between 10 and 20 Hz). This example, however, involves important specializations of the sonic muscle and swimbladder: the sonic muscle has a hook that is attached to a small tubercle of the swimbladder wall at rest (Parmentier et al, 2006a), and muscle fibers and myofibrils have a unique helical disposition (Parmentier et al, 2003). Here, sound frequency is not determined by the contraction rate of the sonic muscle (Parmentier et al, 2006a).…”
Section: Introductionmentioning
confidence: 99%
“…In Carapus acus (Carapidae), Parmentier et al (Parmentier et al, 2006a) demonstrated that sonic muscles inserting on the swimbladder can also produce sounds at very low contraction rates (sonic muscle tetanized between 10 and 20 Hz). This example, however, involves important specializations of the sonic muscle and swimbladder: the sonic muscle has a hook that is attached to a small tubercle of the swimbladder wall at rest (Parmentier et al, 2006a), and muscle fibers and myofibrils have a unique helical disposition (Parmentier et al, 2003). Here, sound frequency is not determined by the contraction rate of the sonic muscle (Parmentier et al, 2006a).…”
Section: Introductionmentioning
confidence: 99%
“…The sound organ of M. furnieri, just like that of other members of the family Sciaenidae, Cynoscion regalis and Kathala axillaris (Connaughton et al, 1997;Veerappan et al, 2009), or members of other families like Carapidae, Carapus acus (Parmentier et al, 2003), consists of a swim bladder and a pair of extrinsic muscles.…”
Section: Discussionmentioning
confidence: 99%
“…This air sac has an anterior thinner zone of its wall called the swim bladder fenestra. This is situated just under the swim bladder plate, which is an osseous enlargement of the third epineural (Parmentier et al 2003a(Parmentier et al , 2006b). During muscle contraction, the thinner zone allows the rostral displacement of the most anterior part of the swim bladder only and the stretching of the swim bladder fenestra (Parmentier et al 2003a(Parmentier et al , 2006b.…”
Section: Galley Proofmentioning
confidence: 99%
“…Parasite species feed on the internal tissues of their host, mainly the gonads (Arnold 1956, Trott 1970, Parmentier and Das 2004, Parmentier and Michel 2013. Another interesting aspect of this group of fishes is their ability to produce sounds (Parmentier et al 2003a,b, 2008, Kéver et al 2014. In captivity, series of pulsed sounds have been recorded for Carapus boraborensis (Kaup, 1856), Carapus homei (Richardson, 1846), and Encheliophis gracilis (Bleeker, 1856), only after an individual had entered a sea cucumber that was already occupied by a conspecific or a heterospecific organism (Parmentier et al 2003b, Lagardère et al 2005).…”
mentioning
confidence: 99%